RESTORATIVE APPROACH AS AN ALTERNATIVE TO RESOLVING DIGITAL HEALTH SERVICE DISPUTES - Handojo Dhanudibroto; Gunawan Widjaja; Hotmaria Hertawaty Sijabat (Adisam Publisher, 2025)
The restorative approach as an alternative to resolving digital health service disputes offers a new paradigm that focuses on restoring relationships between patients, healthcare providers, and the community. Unlike litigation mechanisms, which tend to be repressive, this approach emphasises dialogue, mutual agreement, and openness without pressure, thereby creating fair and dignified solutions for the parties involved in the dispute. In the context of digital health, the application of restorative justice is becoming increasingly relevant due to the growing complexity of disputes arising from the use of information and communication technology, as well as the need to protect the rights of patients and medical personnel. This study aims to examine the effectiveness and challenges of implementing a restorative approach as an alternative to resolving digital health service disputes in Indonesia. Using normative legal research and literature review methods, this study analyses relevant regulations, international practices, and obstacles faced in the implementation of restorative justice-based non-litigation mechanisms. The findings indicate that restorative justice has great potential to enhance public trust, improve dispute resolution efficiency, and provide legal protection for all parties. However, it still faces challenges such as regulatory fragmentation, data privacy protection, and digital literacy gaps. Thus, the study emphasises that synergy between the government, service providers, health workers, and the community is essential to strengthen regulations, infrastructure, and human resource capacity in supporting the effective and sustainable implementation of restorative approaches. Therefore, restorative justice can be an adaptive and equitable solution in resolving digital health service disputes in the current era of technological transformation.